Ryegrass straw and wood shavings as bulking agents on swine slurry coâcomposting: a case study in Southern Brazil - Luana Goulart Sardá; Martha Mayumi Higarashi; Paulo Armando Victória De Oliveira; Jucinei José Comin (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Adoption of co-composting to treat swine slurry can reduce risks of pollution and produce organic fertilizer. Wood shavings and sawdust are the usual bulking agents used in such treatments, however planted forest is a feedstock source of slow renewability rate. Thus, the prospection of alternative biomass feedstock in regions of high animal density, may enable the pig slurry co-composting. Therefore, this manuscript describes a case study carried in Southern Brazil, region that houses 56% of Countryâs swine herd, and where ryegrass is a common winter cover crop. Method A study was conducted to evaluate the effect of increasing shares of ryegrass straw in the bulking agent of swine slurry co-composting, as follow: wood shaving (W), ryegrass straw (S) and blends (W/S=50/50 and 30/70). Composting evolution was monitored during 85 days by measuring daily the temperature and emissions of CO2, CH4 and NH3, afterwards at 100th day the resulting composts were characterized. Results The increase in straw shares, elevated temperature peaks (>60° C), accelerated the biomass stabilization from >85 to 65 days, and produced fertilizers with higher nutrient content due to its higher biodegradability, though NH3-N emission increased up to10%. The maintenance of a share of wood shavings can mitigate that emission, besides improve the stability of pile temperature and decrease leaching. Conclusion Although ryegrass straw can total or partially substitute wood shavings in swine slurry co-composting, substrates blends were more promising. Further studies approaching management adjusts are required to prevent increasing the emission of NH3-N and leaching.